Sharp Estimates of the Embedding Constants for Besov Spaces - Evans, W. Desmond; Karadzhov, Georgi E.; Edmunds, David E. (Revista Matemática Complutense, 2006)
Sharp estimates are obtained for the rates of blow up of the norms of embeddings of Besov spaces in Lorentz spaces as the parameters approach critical values.